2003
DOI: 10.1007/s00125-003-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Rates and risks for co-morbid depression in patients with Type 2 diabetes mellitus: results from a community-based study

Abstract: Aims/hypothesis. There is accumulating evidence that depression is common in people with Type 2 diabetes. However, most prevalence-studies are uncontrolled and could also be inaccurate from selection-bias, as they are conducted in specialized treatment settings. We studied the prevalence and risk factors of comorbid depression in a community-based sample of older adults, comparing Type 2 diabetic patients with healthy control subjects. Methods. A large (n=3107) community-based study in Dutch adults (55-85 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
118
7
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 27 publications
(34 reference statements)
16
118
7
5
Order By: Relevance
“…The negative consequences of depression in diabetes are not restricted to patients who suffer from clinical depression; such consequences are also manifested by diabetic patients who have elevated depressive symptoms [3,5,10]. Furthermore, some prospective studies have demonstrated that non-diabetic people with elevated depressive symptoms have a six-fold higher risk of developing clinical depression in the future [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The negative consequences of depression in diabetes are not restricted to patients who suffer from clinical depression; such consequences are also manifested by diabetic patients who have elevated depressive symptoms [3,5,10]. Furthermore, some prospective studies have demonstrated that non-diabetic people with elevated depressive symptoms have a six-fold higher risk of developing clinical depression in the future [44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with nondepressed diabetic patients, depressed diabetic patients have poorer glycaemic control [1,2], a higher risk of multimorbidity and mortality [3,4], increased functional impairment [5], and poorer adherence to diet, exercise, and diabetes self-management [6,7]. In addition, coexisting depression has a negative impact on the quality of life of patients with diabetes [8,9] and is associated with a significant increase in total expenditure on health care [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not exclude the possibility that biological factors account for the difference in the prevalence of depression between diagnosed and undiagnosed diabetes. For example, diabetes complications have been linked to the development of depression (Teodorczuk et al, 2010;Pouwer et al, 2003). Unfortunately differences in diabetes-related complications between people with undiagnosed diabetes and this with diagnosed diabetes were not taken into consideration in the above mentioned studies.…”
Section: Prevalence Of Depression In Undiagnosed Diabetesmentioning
confidence: 99%
“…In keeping with the activity restriction model of depression [18], it is postulated that illness-related functional disability and restrictions in activities of daily living (ADL) are responsible for depressive affect. In the context of diabetes, for example, the results of a large community-based study indicate that functional limitations play an important role in the development of depression in people with type 2 diabetes [19]. This finding is of particular relevance to DPN in view of its association with severe physical disability, and in some patient populations it fully accounts for diabetes-related functional limitations [2].…”
Section: Introductionmentioning
confidence: 99%